2010
DOI: 10.1021/jp9105663
|View full text |Cite
|
Sign up to set email alerts
|

Variationally Calculated Vibrational Energy Levels of Ammonia Adsorbed on a Ni(111) Surface

Abstract: We have calculated vibrational energy levels for an ammonia molecule adsorbed on a Ni(111) surface. An exact kinetic energy operator for the gas phase molecule is combined with a potential energy function that is calculated with the plane-wave density-functional theory. The resulting eigenvalue problem is solved variationally. The vibrational energy levels for a gas phase molecule are also calculated. The calculated adsorption-related shift is +193 cm−1 for the symmetric bend, −54 cm−1 for the asymmetric bend,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…1, which combines with Cu (1 1 1) surface on the top site through N atom. Any attempt to find a minimum of energy in the other symmetric sites leads to the top site after complete optimization, which is in agreement with previous theoretical studies of NH 3 adsorption on transition metals [13][14][15][16][17][18][19][20][21][22][25][26][27]. In the preferred adsorption geometry, NH 3 adsorbs on the surface with atomic N downwardly and the C 3 axis of NH 3 is perpendicular to the surface, which is similar to the previous calculation results on Pd (1 1 1) surface [27].…”
Section: Adsorption Configuration Of Relevant Species On Clean and Oxsupporting
confidence: 89%
See 3 more Smart Citations
“…1, which combines with Cu (1 1 1) surface on the top site through N atom. Any attempt to find a minimum of energy in the other symmetric sites leads to the top site after complete optimization, which is in agreement with previous theoretical studies of NH 3 adsorption on transition metals [13][14][15][16][17][18][19][20][21][22][25][26][27]. In the preferred adsorption geometry, NH 3 adsorbs on the surface with atomic N downwardly and the C 3 axis of NH 3 is perpendicular to the surface, which is similar to the previous calculation results on Pd (1 1 1) surface [27].…”
Section: Adsorption Configuration Of Relevant Species On Clean and Oxsupporting
confidence: 89%
“…Bond lengths (Å) Adsorption energies (eV) phenomenon was also confirmed by experiment [6,7,42] and theoretical calculations [13][14][15]23,24,27,33]. For the adsorption of NH 3 on oxygen-covered Cu (1 1 1) surface, it is found that the most stable co-adsorption configuration is that NH 3 adsorbs on the top site and O atom occupies the hcp site ( Fig.…”
Section: Configurationssupporting
confidence: 55%
See 2 more Smart Citations
“…As assignment of spectra is achieved by comparing measured [2] and computed frequencies, it is clear that the ability to compute accurately vibrational frequencies is important for guiding material design. Today, with rare exceptions [3][4][5][6][7], such assignment is based on uncoupled harmonic frequencies provided by widely used DFT codes [8,9]. Anharmonicity and coupling effects can shift frequencies by dozens cm -1 and hinder assignment [3,10], yet their inclusion in calculations has been too computationally expensive for most labs.…”
Section: Introductionmentioning
confidence: 99%